PERAN OMAH TANI DALAM MEMPERJUANGKAN HAK ATAS TANAH PETANI DI DESA TUMBREP KECAMATAN BANDAR KABUPATEN BATANG - Saputra, Lukman Adining (Civic Education Program, Universitas Negeri Semarang, 2017)
This researched purpose to determine Omah Tani efforts in the fight for land rights of farmers in the village of Tumbrep Subdistrict, Batang airport and results Omah Farmers struggle in the fight for land rights of farmers in the village of Batang District of Tumbrep This study used a qualitative research method. Subject of research is the Governing Omah Tani, Tumbrep farmer in the village, the village in the village Tumbrep. Tumbrep village communities. The technique of collecting data using interviews, and documentation. Form of the results of this study conducted by Omah movement Tani divided by 3 (three) kinds of activities. The first activity is to accommodate the masses with a massive amount to do a demonstration. The second form is pursuing legal and audience either with the police, Kejari and also members of the regional legislature. And the final form that the legal assistance when farmers face a trial related to land disputes. The outcome of the struggle Omah Tani is the completion of several land disputes and assist the process of claim PT. Tratak plantations to farmers, and the Omah Farmers can win the lawsuit. On December 18, 2014 came out the decision of the head of the National Land Agency Centre No. 7 / PTT-HGU ​​/ BPN-RI / 2013, which decided that the concession No. 1 / Rod on behalf of PT. Tratak plantation has been established as wastelands. The decision is based on the land area of ​​approximately 79.841Ha can be utilized Agrarian Reform or society